(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The work audits the feasibility of demolished concrete as partial substitute of natural coarse aggregate respectively. In initial stage, same optimum ratio of cement is added with partly replaced natural coarse aggregate (NCA) with recycled concrete aggregate (RCA) in concrete. For test intent, recycled aggregates were accessed from crushed concrete cubes of grade M25 in laboratory. Variant composition of natural coarse aggregate and recycled aggregate adopted and test samples from this matrix were prepared for the same test as mentioned above. Observations reveal, combination of 90% NCA and 10% RCA in ratio, leads to adequate results